PENGARUH KARAKTERISTIK DEWAN KOMISARIS TERHADAP KINERJA KEUANGAN PERUSAHAAN. STUDI KASUS PADA BUMN PERSERO TERBUKA TAHUN 2014-2018 - Awal Susmanto; Arief Daryanto; Hendro Sasongko (School of Business, Bogor Agricultural University (SB-IPB), 2021)
In the corporate governance mechanism, the board of commissioners with its characteristics has a strategic role to increase the value of the company through the process of monitoring the management of the company by the board of directors. This study aims to analyze the effect of the characteristics of the board of commissioners on company performance (ROE and Tobin's Q) in public listed SOEs on the IDX for the 2014-2018 period. By using panel data regression analysis, the results show that the number of independent commissioners and the age of the board of commissioners has a significant positive effect on firm performance (ROE and Tobin's Q), while the educational level of board members and board meetings has a positive effect on ROE but has a negative effect on Tobin's Q. Meanwhile, the number of commissioners does not have a significant effect on ROE, but has a positive effect on Tobin's Q. The findings of this study can be used as a consideration for shareholders, in this case the Ministry of SOEs for the improvement of corporate governance mechanisms, especially in the aspect of the board of commissioners. Keywords: board of commissioner, SOEs, corporate governance, firm financial performance, Ministry of SOEs